Lung carcinoid tumors with Diffuse Idiopathic Pulmonary NeuroEndocrine Cell Hyperplasia (DIPNECH) exhibit pejorative pathological features. (June 2021) - Prieto, Mathilde; Chassagnon, Guillaume; Lupo, Audrey; Charpentier, Marie-Christine; Cabanne, Eglantine; Groussin, Lionel; Wislez, Marie; Alifano, Marco; Fournel, Ludovic
Highlights: Lung carcinoid tumors associated with DIPNECH is a rare condition. The rate of atypical carcinoid tumors subtype is significantly higher in patients with DIPNECH compared to others. Mediastinal lymph-nodes (pN2+) invasion is more frequently associated to resected carcinoid tumors in DIPNECH patients. Abstract: Introduction: Diffuse Idiopathic Pulmonary NeuroEndocrine Cell Hyperplasia (DIPNECH) is a rare disease often associated with carcinoid tumors. We aimed at evaluating the impact of DIPNECH on characteristics and prognosis of patients who underwent radical treatment of pulmonary carcinoid tumors. Material and methods: We reviewed all patients operated on for curative-intent resection of carcinoid tumor in our department from 2001 to 2020. Cases exhibiting both pathological and radiological features of DIPNECH, as assessed by respective thoracic expert physicians, were analyzed separately. Results: 172 cases of resected carcinoid tumors were identified, including 25 (14.5 %) harboring pathological criteria of DIPNECH and radiologic features like mosaic attenuation (92.0 %), multiple nodules < 5 mm (76.0 %), and mucoid impactions (32 %). In DIPNECH patients, major pulmonary resections were usually performed (92.0 %) and resected tumors were mostly classified as pT1 (92 %). Mean Ki67 staining was 3.7 ± 5.2 %. The early postoperative period was mostly uneventful (96.0 %) and 5-year survival was 92.9 ± 6.9 %. Compared to non-DIPNECH cases, we found that patients were older (mean 65.6 ± 9.3 versus 54.1 ± 17.9, p = 0.002), more frequently female (84.0 % versus 56.5 %, p = 0.009), and exhibiting diabetes mellitus (45.8 % versus 18.5 %, p < 0.001) or hypertension (45.8 % versus 24.1 %, p = 0.039). The rate of atypical carcinoid tumors was significantly higher in DIPNECH patients (40.0 % versus 19.9 %, p = 0.027), as well as rate of mediastinal lymph-nodes involvement (pN2+) (36.0 % versus 4.1 %, p < 0.001). At multivariate analysis, only DIPNECH pattern and atypical histology were independent factors of pN2 invasion which was the only predictor of poorer prognosis on Log-Rank test. Conclusion: Carcinoid tumors with proven DIPNECH are associated with negative pathological features and may deserve a dedicated perioperative management.